KONSEP KEPEMILIKAN HARTA DALAM ISLAM - Ratna Ayu Wijayanti; Riki Zogik Firmansyah; Mochamad Rizal Anwar; Renny Oktafia (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Property in Islam is a significant concept that encompasses various aspects such as ownership, distribution, and utilization. Islam emphasizes the importance of legal and transparent ownership, where wealth must be acquired through honest and ethical means. Unethical practices like theft and usury are strictly prohibited. Fair distribution of wealth is also emphasized, as seen in the obligation of zakat, a mandatory payment given to those in need. Islam promotes the idea that wealth should not be selfishly retained by a few, but should be fairly distributed to benefit society as a whole. Additionally, Islam highlights responsible utilization of property. While recognizing individual property rights, Islam also emphasizes the responsible and conscientious use of wealth. Overall, the concept of property in Islam is grounded in principles of integrity, fairness, and responsible stewardship.